Research on the volatility spillover effects of geopolitical conflict risks on international shipping and crude oil markets - Chi, Xiaoying; Zheng, Ruimin; Chen, Yangkexu; Xiao, Guangnian (Frontiers in Marine Science, 2025)
The international shipping market, as a vital pillar of global trade, is closely intertwined with the crude oil market. Geopolitical conflicts—through mechanisms such as supply disruptions, rising transportation costs, and heightened market uncertainty—intensify volatility in both markets and amplify their mutual spillover effects. Using data from November 1999 to August 2025 across three markets, this study applies the Diebold–Yilmaz (DY) spillover index and the DCC-GARCH model to analyze the dynamic linkages between the shipping and crude oil markets, with a particular focus on volatility spillovers among the three. The results show significant bidirectional volatility spillovers between international shipping and crude oil markets, with the strongest spillovers occurring within the shipping market itself, reflecting its high degree of internal interconnectedness. Geopolitical conflict risk acts mainly as a net receiver of volatility and, by triggering supply–demand imbalances, prompting behavioral adjustments, and generating lagged policy effects, further amplifies spillovers between shipping and oil markets. This study not only provides a new perspective for understanding the interdependence of global energy and shipping markets under geopolitical uncertainty, but also offers valuable decision-making implications for policymakers and market participants in managing risks.